2022
DOI: 10.3389/frph.2022.863695
|View full text |Cite
|
Sign up to set email alerts
|

Varicocele: An Endocrinological Perspective

Abstract: Varicocele affects 15% of male population but it is more frequently identified in patients searching medical care for infertility. The impact of varicocele on semen production and fertility is known, but the relationship between clinical varicocele and impaired hormonal production is not clear. In published literature there are some studies regarding hormonal alterations in patients with varicocele but no review in which all the hormonal findings are explained. The aim of this review is to evaluate, by most co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 52 publications
(62 reference statements)
1
0
0
1
Order By: Relevance
“…In this study, it was possible to observe an association between vitamin D deficiency and elevated alkaline phosphatase levels (OR 3.50; 95%CI 1.20-10.17); similar results were seen in an Italian study of 230 patients, which observed a negative correlation between insufficient levels of 25(OH)D and alkaline phosphatase (r=-0.2; p=0.0008) 23 .…”
Section: Discussionsupporting
confidence: 87%
“…In this study, it was possible to observe an association between vitamin D deficiency and elevated alkaline phosphatase levels (OR 3.50; 95%CI 1.20-10.17); similar results were seen in an Italian study of 230 patients, which observed a negative correlation between insufficient levels of 25(OH)D and alkaline phosphatase (r=-0.2; p=0.0008) 23 .…”
Section: Discussionsupporting
confidence: 87%
“…La probabilidad de que el paciente sufra complicaciones después de haber realizado la cirugía es muy baja, pero se ha notado que la trombosis de la vena renal, epididimitis, varicoceles recidivantes, hidrocele postoperatoria y el dolor en los testículos son síntomas que se han visto hasta 10 días después de haber realizado el tratamiento (4,17).…”
Section: Complicacionesunclassified
“…Sperm DNA fragmentation decreases the outcome of in vitro fertilization (IVF), natural conception, and intrauterine insemination. Reparation of varicocele by surgical procedure significantly increases sperm quality in around 60% of males with infertility [ 4 ].…”
Section: Introductionmentioning
confidence: 99%